Windows Azure web sites - Chambers, James (John Wiley & Sons, 2013)
A no-nonsense guide to maintaining websites in Windows Azure If you're looking for a straightforward, practical guide to get Azure websites up and running, then this is the book for you. This to-the-point guide provides you with the tools you need to move and maintain a website in the cloud. You'll discover the features that most affect developers and learn how they can be leveraged to work to your advantage. Accompanying projects enhance your learning experience and help you to walk away with a thorough understanding of Azure's supported technologies, site deployment, and manageme.